A tissue-selective estrogen complex as treatment of osteoporosis in experimental lupus. (February 2022) - Nordqvist, Jauquline; Engdahl, Cecilia; Scheffler, Julia M; Gupta, Priti; Gustafsson, Karin L; Lagerquist, Marie K; Carlsten, Hans; Islander, Ulrika
Osteoporosis is a common secondary complication in patients with systemic lupus erythematosus (SLE). Current osteoporosis treatment with bisphosphonates has some negative side effects and there is a lack of data regarding newer treatments options for SLE associated osteoporosis. The tissue-selective estrogen complex (TSEC) containing conjugated estrogens and the selective estrogen receptor modulator bazedoxifene (Bza) is approved for treatment of postmenopausal vasomotor symptoms and prevention of osteoporosis. However, it has not been evaluated for treatment of osteoporosis in postmenopausal SLE patients. Ovariectomized MRL/ lpr mice constitute a model for postmenopausal lupus that can be used for osteoporosis studies. We used this model in a set of experiments where the mice were treated with different doses of 17β-estradiol-3-benzoate (E2), Bza, or TSEC (E2 plus Bza), administered in the early or late phases of disease development. The skeleton was analyzed by dual-energy X-ray absorptiometry, peripheral quantitative computed tomography, and high-resolution microcomputed tomography. The lupus disease was assessed by determination of proteinuria, hematuria, and lupus disease markers in serum. Treatment with medium dose TSEC administered in early disease protected ovariectomized MRL/ lpr mice from trabecular bone loss, while there were no differences in lupus disease parameters between treatments. This is the first experimental study to investigate TSEC as a potential new therapy for osteoporosis in postmenopausal SLE.